Association Between Maternal Height and Childhood Stunting in Indonesia: A Systematic Review - Yanasta Yudo Pratama; Muhammad Luthfi Adnan (Epidemiology and Society Health Review (ESHR), 2026)
Background: Stunting is one of Indonesia's most complex health problems with the incidence of stunting reaches almost 30%. Maternal factors are known to play a significant role in the risk of stunting. However, further analysis of the influence of maternal height is needed to identify the influence of maternal height on child growth and development for future intervention. This study aims to evaluate maternal height as risk factor for stunting in Indonesia based on previous published article. Method: This systematic review was prepared in accordance with the PRISMA guidelines. The literature search was conducted in PubMed and Google using keywords in English including "maternal height", "maternal stature", "stunting" and "Indonesia", while keyword in Bahasa Indonesia using "tinggi badan ibu" and "stunting." The search was limited to English and Indonesian language studies with included studies published after 2020. Results: Of the 581 studies identified from two electronic search engines, seven studies met our inclusion criteria. A total of 703 population samples from seven included studies were analyzed regarding the relationship between maternal height and stunting. Five of the seven included studies showed that maternal height influenced the risk of stunting Although maternal height is correlated with the risk of stunting, analysis of the causes of low maternal height is necessary for planning further interventions. Conclusion: Maternal height influences the risk of stunting. However, maternal influences can also influence prenatal growth and development. Long-term studies and interventions are needed to analyze the maternal role in stunting risk.